Power Control of High Penetration PV in Distribution Network - Saman Hosseini Hemati; Ashkan Mohammadi (Institute of Advanced Engineering and Science, 2015)
Photovoltaic energy is one of the fastest growing renewable energy sources in the worldand as the issue of energy security is becoming more and more important it could be a promising option. But as photovoltaic energy is becoming widespread and penetration level of photovoltaic power plants increase, issues rise in distribution networks.In this paper a power control scheme for a high penetration photovoltaic power plant in a radial distribution network will be presented. This control scheme includes an efficient Maximum Power Point Tracking (MPPT), DC link voltage control by managing power balance between the hysteresis controlled inverter and a boost converter. Another aspect of High Penetration PV (HPPV) which is overvoltage in Point of Common Coupling (PCC) is also investigated and maximum allowable Penetration Level (PL) will be determined. Simulations have been done in Matlab/Simulink environment.